Bioinspired nacre-like hierarchical chitosan/hydroxyapatite coatings by electrophoretic deposition - Baştan, Fatih E.; Akhtar, Muhammad Asim; Krapf, Anna; Roether, Judith; Beltrán, Ana M.; Göken, Mathias; Boccaccini, Aldo R. (Applied Materials Today, 2026)
Nacre's unique microstructural arrangement, hierarchical alternating stackings of organic molecules and inorganic platelets, yields superb mechanical efficiency beyond the predictions of the rule of mixture. In this study, we produced ordered chitosan (CS)/hydroxyapatite (HA) coatings by electrophoretic deposition (EPD), mimicking the nacre's hierarchical brick-and-mortar microstructure. To build such a hierarchic structure, we used platelet-shaped HA particles oriented in the (100) plane, which obviated the common need for 2d templates for creating nacre-mimetics. The coatings showed an ordered and layered structure of the HA plates (64–86 wt.%) mediated by CS molecules, resulting in a superior elastic modulus (12 GPa) and relatively high wear resistance. The coatings were also a perfect platform for rapid apatite formation and pre-osteoblast cell proliferation. After 7 days, the cell population on the coatings was nearly doubled relative to that on plain stainless steel. The collective benefit of outstanding mechanical performance and superior in vitro performance of the CS/HA coating was conferred by the nacre mimetic design. This study can pave the way for expanding the use of the nacre motif in electrophoretically deposited biomedical coatings.
CRIS-Team Scopus Importer:2025-12-12
Keywords: Biomimetic; Nacre; Nanoindentation; Oriented deposition